Application Of Predialytic Exercise To Reduce Fatigue In-Patient Undergoing Hemodialysis - Nugroho Lazuardi (South East Asia Nursing Research, 2021)
Chronic kidney disease is an irreversible and slow-progressing disorder of kidney function so that the kidneys are unable to maintain the body's metabolism, fluid and electrolyte balance and cause uremia which requires dialysis or kidney transplantation. Hemodialysis is management to treat chronic kidney disease that is carried out for life so that the complications that often arise are fatigue, cramps, anxiety, pain. The phenomenon found in the Hemodialysis Room of the Tugurejo Hospital Semarang, there were 34% of the 84 patients who experienced fatigue which was characterized by lethargy, weakness, drowsiness, dizziness. This research is a quantitative study with a quasi-experimental design. The sample size is 4 respondents in the intervention group without a control group. Measurement of the level of fatigue (pre and post-test) using the PFS (Piper Fatigue Scale) which contains 22 subjective statements. Predialytic Exercise intervention is given for 5 sessions with a duration of 10-15 minutes. The results of this study indicate that the fatigue level of hemodialysis patients has decreased after the intervention of predialytic exercise for 5 sessions. The fatigue score of respondents 1 has decreased from a score of 4.8 (moderate fatigue) to 3.2 (mild fatigue), respondent 2 from a score of 6.3 (moderate fatigue) to 4.3 (moderate fatigue), respondent 3 from score 9 (severe fatigue) to 7 (severe fatigue), and respondent 1 from a score of 4.9 (moderate fatigue) to 2.4 (mild fatigue). The results of this study indicate that there is a decrease in each dimension of fatigue levels so that predialytic exercise intervention is effective to reduce fatigue in patients undergoing hemodialysis.